Вплив тріщин на модулі пружності та життєвий цикл асфальтобетону - Ільїн, Ярослав Вікторович (НТУ "ХПІ", 2017)
Наведено результати визначення впливу тріщин на показники міцності при вигині, модуль пружності та протяжність життєвого циклу асфальтобетону під дією постійного навантаження, що дорівнює 20 % від руйнуючого. Дослідження показали, що тріщини впливають на міцністні показники асфальтобетонів. При цьому на ці показники впливає не тільки їх наявність, але й місце їх розташування. У зв’язку з цим, слід попереджувати розповсюдження тріщин по всій площі покриття та його глибині. Особливої уваги слід надавати місцям у яких діє зосереджене навантаження.

In recent years, a number of studies have been conducted in the world devoted to asphalt concrete cracks. The purpose of this work was to determine the effect of cracks that reduce the cross section of the sample, on the design characteristics of asphalt concrete and their most dangerous location relative to the point of application of the load. It was calculated the most dangerous places for the location of propylene, which artificially simulated cracks in asphalt concrete samples when tested on vibrostend. A series of specimens with trial defects was formed to determine how the crack or poorly-treated bitumen shavings could be affected, in addition to being broken down. The results of the study showed that the most dangerous are cracks that are closer to the maximum loads, that is, the coverage of these places closest to the centers of the tracks. Different load patterns showed remarkably different results regarding the strength of asphalt concrete samples when bending and their life cycle. So the most dangerous for asphalt concrete was the application of the entire weight of the load at one point, placed directly above the place of application of an artificial "cracks". It is logical that the most dangerous for the modulus of elasticity was a crack that was applied closer to the maximum moment (according to the diagram of the moments). The results of the study showed that the cracking effect on the strong sleep characteristics of asphaltic concrete. At the same time, these indicators affect not only their availability, but also the location of their location. In this regard, the distribution of cracks across the coverage area and its depth should be avoided. Particular attention is needed to places where a concentrated load operates.
The influence of cracks on the elasticity module and the life cycle of asphalt concrete
Keywords: міцність при вигині; руйнування; тріщиноутворення; бітум; bending strength; destruction; crack